The cholesterol metabolite 25-hydroxycholesterol activates estrogen receptor α-mediated signaling in cancer cells and in cardiomyocytes. - Rosamaria Lappano; Anna Grazia Recchia; Ernestina Marianna De Francesco; Tommaso Angelone; Maria Carmela Cerra; Didier Picard; Marcello Maggiolini (PLoS ONE, 2011)
The hydroxylated derivatives of cholesterol, such as the oxysterols, play important roles in lipid metabolism. In particular, 25-hydroxycholesterol (25 HC) has been implicated in a variety of metabolic events including cholesterol homeostasis and atherosclerosis. 25 HC is detectable in human plasma after ingestion of a meal rich in oxysterols and following a dietary cholesterol challenge. In addition, the levels of oxysterols, including 25 HC, have been found to be elevated in hypercholesterolemic serum.Here, we demonstrate that the estrogen receptor (ER) α mediates gene expression changes and growth responses induced by 25 HC in breast and ovarian cancer cells. Moreover, 25 HC exhibits the ERα-dependent ability like 17 β-estradiol (E2) to inhibit the up-regulation of HIF-1α and connective tissue growth factor by hypoxic conditions in cardiomyocytes and rat heart preparations and to prevent the hypoxia-induced apoptosis.The estrogen action exerted by 25 HC may be considered as an additional factor involved in the progression of breast and ovarian tumors. Moreover, the estrogen-like activity of 25 HC elicited in the cardiovascular system may play a role against hypoxic environments.